1994
DOI: 10.1111/j.1365-2141.1994.tb04841.x
|View full text |Cite
|
Sign up to set email alerts
|

The transport of two iron chelators, desferrioxamine B and L1, across Caco‐2 monolayers

Abstract: The transport of two iron chelators, desferrioxamine B (DFO) and L1 (1,2-dimethyl-3 hydroxypyridin-4-one) has been studied in vitro using the human adenocarcinoma cell line, Caco-2. The transport of DFO and L1 has also been compared with that of their iron-bound complexes, ferrioxamine (FO) and L1(3)-Fe, respectively. We report an apparent permeability coefficient (Papp) value for DFO of 0.170 x 10(-7) +/- 0.080 cm s-1. The Papp value of L1 was 1.297 x 10(-5) +/- 0.133 cm s-1. The Papp values of their iron bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
(20 reference statements)
2
14
0
Order By: Relevance
“…A similar phenomenon has been recently reported: transport of iron into human intestinal Caco-2 cells is greatly reduced if iron is combined with a membrane-penneable chelating agent, t.2-dimethyI-3 hydroxypyridin-4-one (17). A preliminary experiment confirmed that ~'Fe remained in a supernatant fraction of lhe serum-free medimn supplemented with IDA 100 and 14 times, at least, more than in the supernatant fractions of the media supplemented with GG and DHEG.…”
Section: Discussionsupporting
confidence: 81%
“…A similar phenomenon has been recently reported: transport of iron into human intestinal Caco-2 cells is greatly reduced if iron is combined with a membrane-penneable chelating agent, t.2-dimethyI-3 hydroxypyridin-4-one (17). A preliminary experiment confirmed that ~'Fe remained in a supernatant fraction of lhe serum-free medimn supplemented with IDA 100 and 14 times, at least, more than in the supernatant fractions of the media supplemented with GG and DHEG.…”
Section: Discussionsupporting
confidence: 81%
“…It may be possible that doses higher than 50 mg/kg/day are necessary to fully reduce oxidative stress in the cholesterol diet-fed rabbits as plasma cholesterol levels remained more than ten times higher in the 50 mg/kg deferiprone treated, high-cholesterol group than in controls. Deferiprone has a low molecular weight, is known to penetrate the cells [80], crosses the blood brain barrier in less than 7 minutes after systemic administration [81], yields a peak plasma concentration one hour after oral administration [36], and its cellular uptake is superior to that of deferoxamine [82], another widely known metal chelator.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, as the NAD system comprises the major factor in intracellular antioxidant activity within the RBC, this observation suggests the prooxidant effect of DFO upon the cytosol of RBC[16]. In regard to the mechanism of the prooxidant effect, because DFO is poorly permeable to RBC membrane [3], the action of DFO may primarily originate extracellularly to cause changes in the intracellular NAD redox potential. In fact, this concept of extracellular oxidant stress was confirmed in previously published data using DFO conjugated with starch to increase the molecular weight [13].…”
Section: Discussionmentioning
confidence: 99%